Faktor-Faktor yang Mempengaruhi Kejadian Stunting pada Balita Usia 0-59 Bulan di Desa Sei Tuan - Raisah Adilah; Maziaturrahmah Maziaturrahmah; Nabila Hana; Ridmahsyah Widiya; Mifta Nurjannah; Mutia Azhari (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
Stunting is one of the health problems in Indonesia. Stunting is a condition where toddlers fail to grow due to chronic malnutrition so that the child's height is too short for his age. The purpose of this study was to determine the factors that cause stunting in toddlers in Sei Tuan village. This research method uses quantitative research with a cross sectional research design. Data analysis used univariate and bivariate analysis. The results of this study indicate that parental education, income and exclusive breastfeeding have an effect on the incidence of stunting in Sei Tuan village. Where the father's education variable has a p value of 0.043 (<0.05). Income variable with p value 0.006 (<0.05). Then the exclusive breastfeeding variable with p value 0.002 (<0.05). The conclusion of this study is parental education, income and exclusive breastfeeding are the factors that influence the incidence of stunting in Sei Tuan Village.